DETERMINAÇÃO DE HIDRAZINA POR VOLTAMETRIA DE ONDA QUADRADA SOBRE ELETRODO DE GRAFITE MODIFICADO COM FeTPyPz - Dantas, Luiza Maria Ferreira (2007)
In this work, the determination of hydrazine (N2H4) in aqueous solutions was investigated by voltammetric techniques on pyrolytic graphite electrodes (GP) before and after modification with iron tetra-pyridinoporphyrazine (FeTPyPz). The modified electrode GP/FeTPyPz presented higher oxidation currents and better voltammetric profiles in comparison with the unmodified electrodes. This modified electrode exhibited two reversible peaks attributed to the redox processes: Fe(I)TPyPz/Fe(II)TPyPz and Fe(II)TPyPz/Fe(III)TPyPz. The pH optimization conditions were performed in solutions prepared by the mixture of different proportions of 0.1 mol L-1 sodium hydroxide (NaOH) and 0.1 mol L-1 phosphate buffer solutions in order to obtain solutions with pH varying from 7 to 13. In order to increase the sensitivity for hydrazine oxidation, three voltammetric techniques were tested: cyclic voltammetry (CV), differential pulse voltammetry (DPV) and square wave voltammetry (SWV). The best results were provided by the latter one and the optimized conditions for hydrazine determinations were: i) electrolyte: 0,1 mol L-1 NaOH solution; ii) frequency: 30 s-1; pulse amplitude: 50 mV and scan increment: 8 mV. Under such conditions, the modified electrodes provided linear responses ranging from 5 up to 111 μmol L-1, with detection and quantification limits of 0.82 μmol L-1 and 2.7 μmol L-1, respectively. The investigated sensor presented relative standard deviation values for repeatability and reproducibility lower from 5%. The sensor was applied to analyze boiler water samples and a recovery average of 116 % was found.